(untitled) (Medicine Today, 2026)
Introduction: This study investigates the demographic characteristics, clinical presentations, angiographic findings, and associated risk factors of coronary artery disease (CAD) among 120 patients undergoing coronary angiography at the National Institute of Cardiovascular Diseases. (NICVD). Objective: The primary objective was to analyze the pattern of CAD and assess its correlation with known risk factors in a Bangladeshi population. Methods: This study employed a cross-sectional observational design. It was conducted at the Cardiology Department of the National Institute of Cardiovascular Diseases. (NICVD). The study duration was one year from July 2024 to June 2025. The study aimed to evaluate the relationship between age, sex, and the severity of coronary artery disease (CAD) in patients concurrently diagnosed with type 2 diabetes mellitus and hypertension, using data derived from coronary angiography. Results: The analysis revealed that CAD predominantly affects middle-aged individuals, with a mean patient age of 54.53 years. Males comprised most of the sample, emphasizing a gender disparity in CAD prevalence. Among angiographic patterns, Single Vessel Disease (SVD) was the most common (46.67%), followed by Double Vessel Disease (33.33%) and Triple Vessel Disease (20.00%). The Left Anterior Descending (LAD) artery was most frequently involved (62.12%), underlining its critical role in ischemic heart disease. Hypertension (37.50%) and Diabetes Mellitus (28.33%) were the most prevalent comorbid conditions, both significantly associated with multi-vessel involvement. Most patients presented with effort-related chest pain, while a substantial portion required revascularization interventions including Percutaneous Coronary Intervention (PCI) and Coronary Artery Bypass Grafting (CABG). Conclusion: This study underscores the urgent need for early identification and control of modifiable risk factors such as hypertension and diabetes to prevent CAD progression. The findings are consistent with both regional and global data, offering valuable insights for clinicians and public health policymakers aiming to reduce the CAD burden in South Asia. Limitations include a single-center design and a modest sample size, suggesting the need for larger, multi-center longitudinal studies. Medicine Today 2026, Vol.38 (1): 14-18